2020
DOI: 10.1186/s12874-020-00994-0
|View full text |Cite
|
Sign up to set email alerts
|

A review of the use of propensity score diagnostics in papers published in high-ranking medical journals

Abstract: Background: Propensity scores are widely used to deal with confounding bias in medical research. An incorrectly specified propensity score model may lead to residual confounding bias; therefore it is essential to use diagnostics to assess propensity scores in a propensity score analysis. The current use of propensity score diagnostics in the medical literature is unknown. The objectives of this study are to (1) assess the use of propensity score diagnostics in medical studies published in high-ranking journals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 44 publications
1
30
0
Order By: Relevance
“…We present the first systematic review of the otolaryngology literature to evaluate the use and reporting of PSM methodology. We found systematic underreporting of PSM methodological components in the otolaryngological literature, which is in accordance with findings of other studies in different fields [14,21,[41][42][43].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We present the first systematic review of the otolaryngology literature to evaluate the use and reporting of PSM methodology. We found systematic underreporting of PSM methodological components in the otolaryngological literature, which is in accordance with findings of other studies in different fields [14,21,[41][42][43].…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, one of the limitations of PSM is that it only controls for covariates included in the propensity score. Unlike true randomization, residual confounding can still bias results when important covariates are not identified a priori , or not available for use in the propensity score [ 43 , 45 ]. Additionally, following matching, it is often standard practice to assess any residual inter-group differences through reporting covariate balance.…”
Section: Discussionmentioning
confidence: 99%
“…Standardized differences are an attribute of the sample, independent of the sample size. It is easy to compute and understand and is the most commonly used diagnostic method to measure the balance of covariate distribution between treatment groups (36,38). In our current analysis, all of the 20 observational studies applied PSM or IPTW to balance the covariates between NOACs and warfarin regimen group.…”
Section: Discussionmentioning
confidence: 99%
“…These can be informed by previously published research, pilot studies, or by the investigators' clinical judgment. Granger and colleagues conducted a review of the use of propensity score diagnostics in papers published in the medical literature and noted which studies reported estimates of the c‐statistic of the propensity score model 25 . Similarly, Sturmer and colleagues reviewed the use of propensity score methods in the medical literature 26 .…”
Section: Discussionmentioning
confidence: 99%